Antimicrobial Resistance in Diverse Escherichia coli Pathotypes from Nigeria - Kenneth Nnamdi Anueyiagu; Chibuzor Gerald Agu; Uzal Umar; Bruno Silvester Lopes (MDPI AG, 2024)
Escherichia coli is a gram-negative commensal bacterium living in human and animal intestines. Its pathogenic strains lead to high morbidity and mortality, which can adversely affect people by causing urinary tract infections, food poisoning, septic shock, or meningitis. Humans can contract E. coli by eating contaminated food-such as raw or undercooked raw milk, meat products, and fresh produce sold in open markets-as well as by coming into contact with contaminated settings like wastewater, municipal water, soil, and faeces. Some pathogenic strains identified in Nigeria, include Enterohemorrhagic (Verotoxigenic), Enterotoxigenic, Enteropathogenic, Enteroinvasive, and Enteroaggregative E. coli. This causes acute watery or bloody diarrhoea, stomach cramps, and vomiting. Apart from the virulence profile of E. coli, antibiotic resistance mechanisms such as the presence of blaCTX-M found in humans, animals, and environmental isolates are of great importance and require surveillance and monitoring for emerging threats in resource-limited countries. This review is aimed at understanding the underlying mechanisms of evolution and antibiotic resistance in E. coli in Nigeria and highlights the use of improving One Health approaches to combat the problem of emerging infectious diseases.